The Effect of Training Implementation And Work Discipline Level In Improving Employee Performance At PT. Jasa Raharja (Persero) Medan Branch Office - Irvan Rolyesh Situmorang (LPPM STIE EKA PRASETYA, 2022)
The purpose of this study was to determine whether training and work discipline affect employee performance at PT. Jasa Raharja (Persero) Medan Branch Office. The performance produced by employees at this company is not good, because the training factor which is still considered not good is carried out based on established procedures and work discipline in this case is the high level of employee absenteeism. The population in this study was 50 employees, the sample used was 50 employees.The results showed that there was a positive and significant effect of training on employee performance. For the work discipline variable, there is a positive and significant effect of work discipline on employee performance. For the variables of training and work discipline on employee performance, it was simultaneously obtained that there was a positive and significant effect of training and work discipline on employee performance at PT. Jasa Raharja (Persero) Medan Branch Office. The magnitude of the effect of training and work discipline on employee performance can be seen from the value of R Square which means that there is an effect of training and work discipline on employee performance. Apart from training and work discipline, there are other influences that affect employee performance such as compensation, leadership style, motivation and other variables.